GAMBARAN PENERIMAAN ORANG TUA DENGAN ANAK RETARDASI MENTAL DI SEKOLAH LUAR BIASA (SLB) C “DG” DAN SLB C “SJ” - Hadi Kosasih (Psibernetika, 2016)
Mental retardation is disability of intelectual functioning and maladaptive behaviour during development. There are some parents can accept their children but there’s also parents that can’t accept the reality to have children with mental retardation. The purpose of this research is knowing parental acceptance who have child with mental retardation. The research use quantitative method, use a questionaire to collect data. The subject of this study is the parents who have mental retardation children in SLB DG and SLB SJ as many as 62 parents.Validty test results with product moment correlation was obtained 34 valid items with validity coefficients range from 0.252 up to 0.817. reliability test results obtained by the cronbach alpha reliability coefficient 0.950. The result is parents have low parental acceptance (48%) towards the mental retardation condition of their children. Factors that influence the parental acceptance are a lack understanding about mental retardation, unpreparedness to face the child’s condition, less communication in family, and negative perception about the child limitation. Keywords : parental acceptance, mentally retarded child